From Palmerston to Disraeli (1856-1876) - Harding, Ewing; Bell, Kenneth (Kenneth Norman), 1884-1951; Winbolt, S. E. (Samuel Edward), 1868-1944 (Salt Lake City, UT : Project Gutenberg, 2016)
"From Palmerston to Disraeli (1856-1876)" compiled by Ewing Harding is a historical account written in the early 20th century. The volume is part of a series intended as a sourcebook for English history, focusing specifically on the crucial period of British politics and society between two prominent Prime Ministers, Lord Palmerston and Benjamin Disraeli. This work appears to compile various documents, letters, and reports relevant to understanding the political climate and significant events during this era. The beginning of the volume outlines its purpose as a resource for students and teachers of history, emphasizing the value of primary sources in understanding the past. It notes that the book is structured chronologically, presenting various significant excerpts such as treaties, parliamentary debates, and correspondence from notable historical figures. Specific early entries include the Neutrality of the Black Sea Treaty, details about military operations in India, and discussions about military reforms, providing a rich tapestry of contemporary political life and the challenges faced in the British Empire over this transformative twenty-year interval. (This is an automatically generated summary.)
Release date is 2016-12-12
E-text prepared by Charlie Howard and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Great Britain -- History -- Victoria, 1837-1901 -- Sources